Exploring the use of flipped learning approach in teaching grammar - Aisyah Hanum, Abu Bakar; Noor Azlinda, Zainal Abidin; Zuraina, Ali; Nursyaheedah, Muhammad Isa; Nor Suhardiliana, Sahar (2018)
Defined as an inverted method in teaching and learning, a flipped learning approach is conducted when the delivery of the content is done at homes by the students and practices are done during class time (Bergmann & Sams, 2012; Sohrabi & Iraj, 2016). Although widely known among tertiary level students, the use is now extended to primary and secondary school students. Assisted by technology and facilities provided in schools, flipped learning approach can provide school students with vast opportunities to engage in English classes, particularly in reading, writing, listening and speaking and also grammar knowledge. Thus, the aim of this study is to highlight the advantages of applying flipped learning approach in English classes, particularly in teaching grammar and to identify the drawbacks that hinder the maximum use of flipped learning approach.